STABILITAS KONSENTRASI GLUKOSA DARAH SIMPAN JANGKA PENDEK DALAM TABUNG BERTEKNOLOGI PEMISAH JELl - Furqon, Ayi; Nurmukhlis, Hilman; Kasiman, Sussylawati (Pharmaciana, 2015)
Serum  glucose  level  is  screening  for  diabetic  patients.  Preanalitical  factors  such  as  sample preparation  and  handling  will  influence  the  quality  of  final  result  of  determination.  Gel  sparation technology used for faster sparation between plasma  or serum and  blood cells. This  technology was applied in clinical laboratory technology in stead of public health laboratory. Requested test of glucose level  determination  is  higher  then  other  analytes. Direct  contact  of  blood  cells  to serum  will  reduce availability  of  glucose  in  serum  due to  glycolysis  process as  well  as  without  additional  enzyme inhibitors  such as  fluoride  and  without  separating  cells  from  serum  immediately. Serum separating Tube (SST)contains gel and clot activators, it will work faster than plain tube does to become serum. Main  purpose  of  research,how  stability  of  glucose  level  between  SST  tube  and  plain  tube . Experimental steps   are preparing fresh   blood that   is  collected   from 16 voluntered   students, incorporating the glucose oxidase enzymatic assay and quality control. Test performed at immediately late 4 hours, and very late 12 haours. Statistical method for the time to time analysis, one way Anova is  used within significant level 0.05. From 16 serum (duplicates), glucose serum level was reduced early at 4 -12 hours by 8,1  mg/dl  (p-value  =  0.013) and  7,7  mg/dl  (p-value  0.012).  Percents increases  of glucose level within plain tube  4 hours by 4,75% and within 12 hours by 13,12%. The increased serum glucose  level  in SST  tube were  at  early 4 hours and 12 hoursby 4,33%  and 12,29% respectively. Conclussion, glucose serum level is in steady at room temperature until 4 hours for both SST Tube as well as plain tube.